Role of stratifin (14-3-3 sigma) in adenocarcinoma of gallbladder: A novel prognostic biomarker. (March 2020) - Sirivatanauksorn, Vorapan; Dumronggittigule, Wethit; Dulnee, Benjamaporn; Srisawat, Chatchawan; Sirivatanauksorn, Yongyut; Pongpaibul, Ananya; Masaratana, Patarabutr; Somboonyosdech, Chayapol; Sripinitchai, Sirinapa; Kositamongkol, Prawat; Mahawithitwong, Prawej; Tovikkai, Chutwichai; et al.
Abstract: Background: Gallbladder cancer (GBC) is a rare and fatal biliary tract malignancy. Genetic derangements are one of many factors that determine the prognosis of GBC. In this study, the expression of the stratifin ( SFN ) gene encoding 14-3-3 sigma protein, which is reported to be associated with the metastatic property of cholangiocarcinoma cells, was investigated in GBC. Material and methods: Formalin-fixed paraffin-embedded cancer (n = 37) and non-cancer control tissues (n = 14) of gallbladders from patients who underwent surgical resection from January 2006 to May 2015 were retrieved. The expression of SFN normalized with that of ACTB was determined using RT-qPCR. Multivariate analysis of factors affecting disease-free survival (DFS) and overall survival (OS) including the type of SFN expression was performed. Result: The average expression level of SFN in cancer was higher than that in control tissues (p = 0.002). The relative SFN expression in cancer tissue was classified as overexpression (n = 14) and control level expression (n = 23) according to the receiver operating characteristic (ROC) curves for discriminating early GBC recurrence or metastasis after surgery. The SFN overexpression group was associated with lower rates of distant metastasis and early tumor recurrence following resection. The univariate analysis demonstrated factors affecting DFS, including resection margin (p < 0.001), lymphovascular invasion (p = 0.040), perineural invasion (p = 0.046), and SFN expression (p < 0.001). The multivariate analysis revealed that the resection margin (p = 0.019) and SFN expression (P = 0.040) were independent prognostic factors of DFS. Conclusion: To achieve the longest survival, margin-free resection is recommended. The overexpression of SFN in GBC is associated with better prognosis, lower rates of early cancer recurrence, and distant metastasis following resection. SFN expression might be a novel prognostic biomarker in GBC treatment. Further studies to elucidate the role of SFN might unveil its clinical benefit in cancer treatment regimens. Highlights: This article is the first to demonstrate a novel prognostic biomarker, stratifin ( SFN ), on gallbladder cancer (GBC) treatment. The benefit to predict cancer recurrence of SF N might be an indication for systemic treatment after resection. Due to the scarcity of a targeted drug to treat GBC, SFN should be investigated as a new targeted treatment in the future.